1 answer:
Answer:
(1,1) is a solution of the system.
Step-by-step explanation:
Let's solve the system.
y = 2x - 1
5x - 4y = 1
In the first equation, y is already separated as a function of x. So we replace in the second equation;
5x - 4(2x - 1) = 1
5x - 8x + 4 = 1
4 - 1 = 8x - 5x
x = 1
y = 2x - 1 = 2(1) - 1 = 1
(1,1) is a solution of the system.
You might be interested in
Answer:
-14 and 4
Step-by-step explanation:
add and subtract 9 from -5
51 is the answer
hope its help
Answer:It would be 3/5 as well.
Step-by-step explanation:
a^4+2a+8 because if you combine like terms that is what you get
The converse of a conditional statement switches the hypothesis and conclusion.